Evolution of agricultural activities in the coastal areas of Romania: Case study Tulcea county - Steliana Rodino (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Coastal areas are commonly defined as the interface or transition areas between land and sea, including large inland lakes. Coastal areas are diverse in function and form, dynamic and do not lend themselves well to definition by strict spatial boundaries. Unlike watersheds, there are no exact natural boundaries that unambiguously delineate coastal areas. On land, the coastal area is increasingly used for intensive agriculture, industry, energy generation electric, mining, transport, development urban and, of course, tourist activities. Inside the hinterland, the agriculture is the main one way of exploiting the land, being a source important income for the rural comunity. The agricultural activities in the coastal areas of romania are subjected to regulatory framework law 202/2002. Rural areas occupy more than 50% of Europe's surface, housing more than 20% of the population. Rural areas play an important role in the national and European regional economy, looking for natural resources and offering jobs through agro-food, tourism, and processing industries. However, rural areas face many challenges such as global competition, automation, market dynamics and, last but not least, environmental challenges. According to national regulatory framework rural areas from Romania occupy 87,1% of the country surface, with 43,7% of total population. This article is an overview of the evolution of agricultural sector in the coastal area in the covering the last three decades.
Keywords: Q10; R14; 330; Romania; coastal area; agriculture